Some comments on the use in research of standard statistical indicators (first post) - Сутула [Vasilij Sutula] Василь Опанасович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if !mso]> <![endif]–> The features of the use of standard statistical data in articles published in leading scientific journals Ukraine and Russia. It is shownthat differentauthors usedifferent symbolsto showthe samestatistical indicators. Confirmed that the characteristics of the studied interval variability of signs should be used where the ratio of statistical indicators marked as follows «Х±σ». It is shown that for a deeper analysis of experimental data is necessary to use the sampling method, which allows to assess the performance characteristics of the sample of the population. <!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>